A Novel Approach in Mold Design in Regards to Weight Reduction of Foam Injection Molded Parts. Issue 5 (September 2013) - Ahmadzai, Ahmad Zia; Behravesh, Amir Hossein; Shahi, Peyman
This paper presents an experimental study on the mold design and the effect of processing parameters on the expansion of foam injection molded parts. Plastic foaming technology has been developed for producing light weight articles along with reducing shrinkage, warpage and sink marks. Limitation in foam expansion is a primary challenge in foam injection molding process. The processing parameters have limited effects on the expansion ratio (or relative density) and cell population density of foam. In this study a novel approach in mold design is introduced to take advantages of concepts such as counter-pressure and mold opening to further extend the expansion range. A modular sheet mold with a rectangular cavity and a fan gate was designed and manufactured. The mold includes a main cavity, the thickness of which could be varied, connected to an overflow channel via a secondary gate, the size of which was also varied in this research. The investigated parameters were part thickness, secondary gate width, blowing agent amount, injection pressure, mold temperature and part thickness. Two-level test experiments were carried out in this research work. The results indicated the high effectiveness of the proposed approach in further reducing the foamed part weight. For the parts with a larger thickness, a noticeable decrease in bulk density and an increase in cell population density along with an improvement in cellular structure uniformity were observed. The expansion was increased as the chemical blowing agent content increased. Other investigated processing parameters, such as injection pressure and mold temperature, had insignificant effects on the relative bulk density within the selected range.